THE APPLICATION OF CATTLE BIOURIN FERTILIZER WITH DIFFERENT DOSE AND FREQUENCY ON THE GROWTH AND YIELD OF Indigofera zollingeriana FORAGE - M., Afandi; Suarna, I W.; Trisnadewi, A.A.A.S. (Jurnal Peternakan Tropika, 2024)
One of the steps to overcome the limitations of forage is to utilize Indigofera zollingeriana legume plants. The long-term use of inorganic fertilizers can damage soil quality. Cattle biourin fertilizer can be an alternative because it contains N (1.4%), P (0.6%), IAA (1852 mg), GA (291 mg), pH (7.45), which is expected to increase the growth of Indigofera zollingeriana.The research aimed to know the effect of giving cattle biourine fertilizer with different dose, frequency, and the interaction to the growth, yield, and plant growth characteristic Indigofera zolligeriana. The research used a completely randomized design (CRD) factorial pattern with two factors. The first factor was the fertilizer doses consist of D0 = 0 liter ha-1, D1 = 3,000 liter ha-1, D2 = 6,000 liter ha-1, D3 = 9,000 liter ha-1, D4 = 12,000 liter ha-1. The second factor was the frequency of fertilizer application consisting of F1 = 1 time and F2 = 2 times so there were 10 experimental units and each unit was repeated 4 times so that 40 experimental units were needed. The variables observed were growth, yield, and growth characteristics. The results showed no interaction between the frequency and dose of cattle biourin fertilizer on all observation variables, the frequency treatment showed the results of F1 tended to be better than F2. The dose treatment of 9,000 liters ha-1 tends to provide the best result for increasing the growth and yield of Indigofera zollingeriana, increasing the dose to 12.000 liter ha-1 still gives a better response but has started to reduce the growth and forage yield of Indigofera zollingeriana. Frequency treatment showed the results of F1 tend to be better at higher doses. The conclution of the study was that there was no interaction between dose and frequency, the dose of 9.000 liters ha-1 tends to yield better result, whilw a single application at a low dosage is better than a twice a week frequency. However, at a high dosage, a twice a week frequency is more effective than a once a week frequency when applying cattle biourin fertilizer of Indigofera zollingeriana.